Rehabilitation by dental implant following a case of focal sclerosing osteomyelitis. A case report - Anitua, Eduardo (2020)
Focal sclerosing osteomyelitis is a rare condition with few therapeutic options other than root canal treatment of the affected tooth. If the tooth is not vital, the treatments are reduced, and there is little scientific evidence of the benefits of the placement of implants in the affected bone. We present a clinical case in which this condition is managed by removing the affected bone, regenerating it with PRGF-Endoret® and subsequently placing a dental implant in the treated area.